Evaluations of the feasibility of oil storage in depleted petroleum reservoirs through experimental modelling studies. (15th June 2021) - Zhao, Xinrui; Al-Abdrabalnabi, Ridha; Wu, Yu-Shu; Zhou, Xianmin
Highlights: Oil storage in depleted reservoir is feasible concept. The withdraw efficiency of the stored oil increases with reservoir porosity, permeability, and BHP. The withdraw efficiency of the stored dead oil reaches 62% during six-month injection. Live oil storage brings higher withdrawal efficiency owing to the existence of the solution gas. Abstract: The global storage space for crude oil is now facing intense challenges due to excess supply. In this situation, increasing oil storage capacity is urgently required. The currently available oil storage facilities, such as tanks and underground caverns, are of limited storage capacity, which cannot be expanded within a short time. Depleted petroleum reservoirs seem to be an ideal alternative since they are geographically ubiquitous and abundant, structurally safe, and cost-effective for storing large amounts of crude oil. Hence, this work aims to investigate the feasibility and approve the concept of oil storage in depleted petroleum reservoirs using both laboratory and modeling approaches. A core flooding experiment was conducted to physically model oil storage and withdrawal in a sandstone core. The results show that around 77% of the stored oil in the core is withdrawn. A core-scale model is then developed to match experimental data and collect inputs for the following studies. A sensitivity analysis is performed to determine the effect of porosity and permeability of the rock and bottom hole pressure (BHP) of the oil injectors on the storage capacity and withdrawal efficiency. The results demonstrate that the storage capacity increases with each of the parameters, but the withdrawal efficiency nearly holds constant. In the Field-scale modeling study, the reservoir stores 7.7 MMbbl oil, and the withdrawal efficiency are 67% and 74% for dead and live oil storage. It indicates oil storage in depleted reservoirs has a great potential to enlarge the global oil storage capacity.